THE DOMINANT OF CHARACTERISTIC OF COMPANY AT THE DISCLOSURE OF INTELLECTUAL CAPITAL (STUDY IN BANKING COMPANY REGISTERED IN BEI PERIOD 2010-2012) - Soewito SOEWITO; Suwandi SUWANDI; Hotma Margaretha Rumapea (UBL, 2016)
Formulation problems in this research is how factors trigger (characteristic of a company) consisting of variable the size of the company, age company, concentration ownership, independent commissioner, and leverage company to the disclosure of intellectual capital. An object research on company banking enrolled in BEI in the 2010-2012. Analysis techniques data using eviews 7. The result of this research showed that in the testing of hypotheses the first, is the significant between variables the size of the company to the disclosure of intellectual capital .Next on the outcome of the testing of hypotheses second is: happened influence significant between variables umur perusahaan to the disclosure of intellectual capital.hasil from the study is the variable the size of the company and the days of company significant to the disclosure of intellectual capital .And variable concentration ownership , independent commissioner , and leverage influential not significantly to the disclosure of intellectual capital.